2021
DOI: 10.1039/d1cc05715d
|View full text |Cite
|
Sign up to set email alerts
|

Development of hypoxia-activated PROTAC exerting a more potent effect in tumor hypoxia than in normoxia

Abstract: In this manuscript, for the first time, we report the development of a kind of hypoxia-activated PROTAC that shows a more potent degradation activity in the tumor hypoxia environment than in normoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…34). 273 They found that compound 212 did not induce the degradation of EGFR protein in normal cells, but the degradation activity of EGFR Del19 was significantly enhanced under hypoxic conditions and it also showed good anti-tumor activity. This is the first example of using hypoxia to activate PROTAC to selectively act on cancer cells, which is providing a new way for the conditionally controlled PROTACs.…”
Section: Design Of Hypoxia-activated Protacsmentioning
confidence: 99%
“…34). 273 They found that compound 212 did not induce the degradation of EGFR protein in normal cells, but the degradation activity of EGFR Del19 was significantly enhanced under hypoxic conditions and it also showed good anti-tumor activity. This is the first example of using hypoxia to activate PROTAC to selectively act on cancer cells, which is providing a new way for the conditionally controlled PROTACs.…”
Section: Design Of Hypoxia-activated Protacsmentioning
confidence: 99%
“…This insufficient oxygen supply results in a hypoxic environment. Recently Cheng et al reported the first Hypoxia-activated PROTAC 121 by using a hypoxia-activated leaving groups (HALGs) to block the EGFR Del19 -based PROTAC (Fig. 17).…”
Section: Conditional Activation Of Protacsmentioning
confidence: 99%
“…reported the identification of a hypoxia-activated PROTAC (PROTAC 45, Table 12 ) by introducing a hypoxia-activated leaving group (1-methyl-2-nitro-1 H -imidazol-5-yl)methyl or 4-nitrobenzyl into the structure of EGFR Del19 -based PROTAC. 93 PROTAC 45 exhibited stronger degradation activity against EGFR Del19 in HCC4006 cells under hypoxia than in normoxia. This was the first example of using tumour hypoxia to identify PROTACs that acted selectively on tumours, providing a new approach for PROTACs development.…”
Section: Protacs For Cancersmentioning
confidence: 91%